The Effectiveness of Placental Drainage in the Active Management of the Third Stage against the Duration of Three Childbirths in the Independent Practice of Midwives in Banda Aceh City - Gustiana, Gustiana; Novemi, Novemi; Yusnaini, Yusnaini; Kartinazahri, Kartinazahri; Fitraniar, Iin (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The third stage of active management has become a standard practice in delivery management. Implementation of childbirth care requires accelerated release of the placenta to avoid bleeding. Placental drainage can shorten the duration of the three stages and reduce blood loss during labor. AIM: The aim of the study is to analyzing the effectiveness of placental drainage in the third stage active management of the third stage of delivery at the midwife’s independent practice (PMB) in the city of Banda Aceh. METHODS: This study used a Quasi Experiment design with a post-test control design. This research was carried out for 12 weeks at the PMB in Banda Aceh City, namely mothers who gave birth at the Erni Munir PMB and the Independent Practice Midwife Mutia Yacob. The sampling technique was purposive sampling. The sample in this study amounted to thirty mothers giving birth, divided into two groups, namely, the treatment group with placental drainage as many as 15 mothers and respondents with cord clamping as many as 15 mothers. With the inclusion criteria, the mother is willing to be a respondent, the vital signs of normal mothers, single and live fetuses, term pregnancy, and an interpretation of average fetal weight ≥ 2500 g. Data analysis used the MannWhitney test, with a confidence level of 95%. RESULTS: The results showed a difference in effectiveness between the placental drainage group and the umbilical cord clamping group, as evidenced by a statistical test with p = 0.001. The length of three stages required by mothers to give birth with placental drainage has a mean value of 4.47 min with a standard deviation of 0.516. The average length of time required by the mother to give birth with umbilical cord clamping is 5.40 min with a standard deviation value of 0.828. CONCLUSION: Placental drainage was more effective than umbilical cord clamping to shorten the third stage length in the Independent Practice of Midwives in Banda Aceh City.